2005
DOI: 10.1007/s11207-005-7417-9
|View full text |Cite
|
Sign up to set email alerts
|

The NOAA Goes-12 Solar X-Ray Imager (SXI) 2. Performance

Abstract: The Solar X-ray Imager (SXI) was launched on 23 July 2001 on NOAA's GOES-12 satellite and completed post-launch testing on 20 December 2001. It was brought into operations on 21 January 2003. This paper documents SXI performance and calibrations prior to an instrument degradation that occurred on 5 November 2003 and thus covers more than 420 000 soft X-ray images of the Sun. This paper details component-level as well as full-system calibrations characterizing the spatial and spectral performance of the instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…SMEI on Coriolis (Jackson et al 2004) provides wide-field coronagraph images from an Earth-orbiting Air Force satellite platform, and is ideally suited for STEREO HI comparisons and in situ comparisons. SXI on NOAA's GOES-M approximates Yohkoh soft X-ray images at a 1-minute cadence in a softer, more sensitive, X-ray band geared toward coronal studies (Pizzo et al 2005). Both these imagers complement STEREO imaging, and enhance IMPACT science by providing a more complete description of the coronal events preceding detected ICMEs.…”
Section: Relationships To Other Missions and Ground-based Observationsmentioning
confidence: 92%
“…SMEI on Coriolis (Jackson et al 2004) provides wide-field coronagraph images from an Earth-orbiting Air Force satellite platform, and is ideally suited for STEREO HI comparisons and in situ comparisons. SXI on NOAA's GOES-M approximates Yohkoh soft X-ray images at a 1-minute cadence in a softer, more sensitive, X-ray band geared toward coronal studies (Pizzo et al 2005). Both these imagers complement STEREO imaging, and enhance IMPACT science by providing a more complete description of the coronal events preceding detected ICMEs.…”
Section: Relationships To Other Missions and Ground-based Observationsmentioning
confidence: 92%
“…This long duration flare started at ≈14:20 UT, after a series of impulsive compact flares occurring over a period of two hours. The 1−8 Å soft X-ray flux peaked at ≈15:20 UT, and during the decay phase, the Solar X-ray Imager (SXI; Pizzo et al 2005) onboard the GOES satellite showed a huge cusped post-eruption loop-system south of NOAA 10652, revealing that the eruption occurred in between NOAA 10652 and NOAA 10653.…”
Section: Application Of the Model To The Cme Of 25 July 2004mentioning
confidence: 99%
“…Solar coronal-hole fractional areas were determined from soft X-ray images acquired by the Soft X-ray Imager (SXI; Hill et al 2005;Pizzo et al 2005) onboard the GOES-12 spacecraft 2 . For our purposes, we used four SXI coronal images per day taken around 0, 6, 12, and 18 UT.…”
Section: Datamentioning
confidence: 99%